2020
DOI: 10.1021/acs.jmedchem.9b01670
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Bromodomain and Extraterminal Inhibitor with a Low Predicted Human Dose through Synergistic Use of Encoded Library Technology and Fragment Screening

Abstract: The bromodomain and extraterminal (BET) family of bromodomain-containing proteins are important regulators of the epigenome through their ability to recognize N-acetyl lysine (KAc) post-translational modifications on histone tails. These interactions have been implicated in various disease states and, consequently, disruption of BET− KAc binding has emerged as an attractive therapeutic strategy with a number of small molecule inhibitors now under investigation in the clinic. However, until the utility of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…2-((1H-Indol-4-yl)methyl)-6-(methylcarbamoyl)isonicotinic Acid (51). tert-Butyl 2-(chloromethyl)-6-(methylcarbamoyl)isonicotinate (50, 1 g, 3.51 mmol) was taken up in 1,4-dioxane (20 mL) and water (10 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2-((1H-Indol-4-yl)methyl)-6-(methylcarbamoyl)isonicotinic Acid (51). tert-Butyl 2-(chloromethyl)-6-(methylcarbamoyl)isonicotinate (50, 1 g, 3.51 mmol) was taken up in 1,4-dioxane (20 mL) and water (10 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Among the bromodomain containing proteins, BET family (BRD2, BRD3, BRD4, and BRDT) has been the most extensively explored and the results of these explorations has ascertained its links with diverse cancers. In light of the aforementioned, the BET family of proteins represents a well-established therapeutic target for oncology and immunoinflammation indications [270][271][272] and numerous small molecule inhibitors capable of abrogating the BET − KAc interactions are currently under clinical investigation (Fig. 7).…”
Section: Bet Inhibitorsmentioning
confidence: 99%
“…In a separate study, DEL screening identified a structurally novel second generation bromodomain and extraterminal (BET) inhibitor using His-tagged BRD4. 26 The hit-to-lead optimization strategy was derived from an analysis of attrition causes for the first generation BET inhibitors as well as the risk of submaximal target engagement for these compounds due to low systemic concentrations following oral dosing. The strategy therefore emphasized physicochemical properties, solubility, and predicted human daily dose.…”
Section: ■ Brd4mentioning
confidence: 99%